THE POSSIBLE APPLICATION FROM CARL HEMPET´S DEDUCTIVE-NOMOLOGICAL EXPLICATIVE MODEL TO THE JON SEARLE´S INSTITUTIONAL FACTS - CASTILLO RODRÍGUEZ, KATHERINE (Disertaciones, 2012)
This work pretends to describe and to evaluate the problem between the scientific explanation from Carl Hempel´s deductive-nomological model and its possible application to John Searle´s institutional facts. In first place, it pretends to show a deductive-nomological explanation, considering in this explanation model a fundamental element that is the laws, which are causal regularities of description. In second place, it will show what are institutional facts and how are they considerate as an essential element to construct a social reality. Finally, why in the institutional facts do not exist a deductive-nomological explanation possibility, since they do not behave in a causal way, but inside them reside the freedom notion.